2018
DOI: 10.1128/iai.00139-18
|View full text |Cite
|
Sign up to set email alerts
|

Immunity against the Obligate Intracellular Bacterial Pathogen Rickettsia australis Requires a Functional Complement System

Abstract: The complement system has a well-defined role in deterring blood-borne infections. However, complement is not entirely efficacious, as several bacterial pathogens, including some obligate intracellular pathogens, have evolved mechanisms for resistance. It is presumed that obligate intracellular bacteria evade complement attack by residing within a host cell; however, recent studies have challenged this presumption. Here, we demonstrate that the complement system is activated during infection with the obligate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…A previous study had shown that the complement system is required for the immune response to Rickettsia infection (Riley et al., 2018). We sought to identify the mechanism of complement activation that occurs during Rickettsia exposure, with the hypothesis that Rickettsia ‐mediated complement activation relies on the classical complement activation pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study had shown that the complement system is required for the immune response to Rickettsia infection (Riley et al., 2018). We sought to identify the mechanism of complement activation that occurs during Rickettsia exposure, with the hypothesis that Rickettsia ‐mediated complement activation relies on the classical complement activation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…C1q −/− mice lack exon 3 of the complement component 1, q subcomponent, alpha polypeptide gene leading to incomplete assembly of the C1 complex and ablation of the entire classical complement activation pathway (Fonseca et al., 2017). WT and C1q −/− mice were intravenously infected with 0.5 minimum lethal doses of R. australis strain Cutlack (Riley et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxic T lymphocyte activities against infected host cells and complement-mediated bacterial killing modulate host-protective immune responses against rickettsial infections (Walker, Olano and Feng 2001 ; Riley et al . 2018 ). Recent studies highlight the critical roles of inflammasome and interferons in fighting against infections caused by Rickettsia (Smalley et al .…”
Section: Discussionmentioning
confidence: 99%